The Giant Gila monster - Kellogg, Ray, -1976; Simms, Jay; Sullivan, Don (Donald E.); Hollywood Pictures Corporation; Cinetel Films ([Los Angeles, CA] : Hollywood Pictures Corporation, 1959)
Youthful hipsters in northern Texas defend the drive-ins and sock hops of the Panhandle from a giant heel of a gila monster.
Originally released as a motion picture in 1959.
Don Sullivan, Fred Graham, Lisa Simone.
Cinematographer, Wilfrid M. Cline; editor, Aaron Stell; music, Jack Marshall.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed November 25, 2015).
Keywords: Gila monster -- Drama; Monsters -- Drama; Teenagers -- Drama; Texas -- Drama; Horror films; Monster films; Science fiction films; Feature films; Internet videos; Streaming video